Divergent fate and roles of dissolved organic matter from spatially varied grassland soils in China during long-term biogeochemical processes - Zhou,P; Tian,L; Siddique,MS; Song,S; Graham,NJD; Zhu,Y-G; Yu,W (Environmental Science and Technology (Washington), 2024)
Terrestrial dissolved organic matter (DOM) is critical to global carbon and nutrient cycling, climate change, and human health. However, how the spatial and compositional differences of soil DOM affect its dynamics and fate in water during the carbon cycle is largely unclear. Herein, the biodegradation of DOM from 14 spatially distributed grassland soils in China with diverse organic composition was investigated by 165 days of incubation experiments. The results showed that although the high humified fraction (high-HS) regions were featured by high humic-like fractions of 4-25 kDa molecular weight, especially the abundant condensed aromatics and tannins, they unexpectedly displayed greater DOM degradation during 45-165 days. In contrast, the unique proteinaceous and 25-100 kDa fractions enriched in the low humified fraction (low-HS) regions were drastically depleted and improved the decay of bulk DOM but only during 0-45 days. Together, DOM from the high-HS regions would cause lower CO2 outgassing to the atmosphere but higher organic loads for drinking water production in the short term than that from the low-HS regions. However, this would be reversed for the two regions during the long-term transformation processes. These findings highlight the importance of spatial and temporal variability of DOM biogeochemistry to mitigate the negative impacts of grassland soil DOM on climate, waters, and humans.